Proceedings of the 2nd International Media Conference 2019 (IMC 2019) 2020
DOI: 10.2991/assehr.k.200325.023
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Fear of Demographic Changes and the Tendency to Spread Viral News Among Millennials

Abstract: Tendency of spreading viral news had become quite a problem in itself, as the information mostly was not authorized, and could trigger the fear of structural changes in the society. This study aimed to investigate whether political preference, religiosity, and group chat involvements affected the tendency to spread viral news, and ultimately led to fear of demographic changes. Quantitatively, 170 youths participated in this study and were analyzed in SEM-PLS. The study found that millennials' political prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that fake and real news spread differently on social media, forming propagation patterns that could be harnessed (Monti et al, 2019). A study found that the millennials' political preference affects their news dissemination; involvement in group chats also increases their news channeling (Abdullah & Syariati, 2020). In Simon et al (2015), social media provides access and timely information during emergency situations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that fake and real news spread differently on social media, forming propagation patterns that could be harnessed (Monti et al, 2019). A study found that the millennials' political preference affects their news dissemination; involvement in group chats also increases their news channeling (Abdullah & Syariati, 2020). In Simon et al (2015), social media provides access and timely information during emergency situations.…”
Section: Introductionmentioning
confidence: 99%